Expression analysis of leptin and leptin receptor in prostate cancer and its association with clinicopathological parameters: A case–control study - Piyush Gupta; Anwesha Banerjee; Amlan Ghos; Dilip K. Pal (Annals of Medical Science and Research)
Aim: The aim of this study is to evaluate the expression analysis of leptin and leptin receptor (LR) in prostate cancer and to determine its association with other clinicopathological parameters. Materials and Methods: Following the screening of the patients fulfilling the inclusion criterion, prostate biopsy specimens were taken and studied. After histopathological diagnosis, immunohistochemistry was done on paraffin-embedded tissue with suitable antibodies. Results were tabulated and analyzed using suitable variables such as mean, median, standard deviation, and Pearson correlation for trend. Results: A total of 77 patients were analyzed out of which 45 were benign and 32 were malignant. Expression of leptin and LR was studied in both benign and malignant tissues and a correlation between these two was found in prostate malignancy which was statistically significant. Conclusion: Our findings concluded that LR expression could be a potential prognostic biomarker for prostate malignancy.